Assessment of Patient Satisfaction in Tertiary Care Allied Hospitals of Rawalpindi Medical University: A Cross-Sectional Study - Younus, Marium; Kamal Khan, Muhammad Adil; Anwar, Azaz; Fatima, Areesha; Azam, Fareeha; Abbasi, Areeb (Students’ Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Patient satisfaction is considered to be a performance measure for the quality of health care services. It is important to maintain a standard of quality care as this has a direct impact on the clinical outcomes of patients. Materials and Methods: This descriptive cross-sectional study was conducted in allied hospitals of Rawalpindi Medical University from April to October 2022. A total of 365 patients from all three allied hospitals of RMU were interviewed through a self-structured questionnaire. A convenience sampling method was used. The data collected was entered and analyzed through SPSS version 25. Frequencies and percentages were used to denote the results. Results: The mean age of the participants was 32.4 years. The mean patient satisfaction score of Benazir Bhutto Hospital was significantly higher than Holy Family Hospital (p= 0.008). The mean patient satisfaction score for District Headquarters Hospital was 90.27. 86.58% of patients were satisfied with the medical care they received in these hospitals and 80.27% of the patients believed the doctor spent adequate time on their check-up. 66.3% of patients were unsatisfied with the availability of drinking water on the hospital premises. Conclusion: The majority of the patients were satisfied with the services provided and the attitudes of medical professionals. There were, however, complaints about the standard of hygiene, lack of medicine, and the long waiting time. Appropriate measures should be taken to improve the conditions in the Allied hospitals of Rawalpindi Medical University to ascertain the provision of quality care and improve health outcomes.